Efektivitas Penggunaan TikTok Shop dalam Meningkatkan Kinerja Pemasaran UMKM Izzata Hijab di Era Digital - Naflah Aurellia Nabilah Firzatullah; Mitha Sintya Dwi Wahyuni; Prima Mufakhoma; Eza Paramitha (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service program aims to analyze the effectiveness of utilizing TikTok Shop as a digital marketing platform for UMKM Izzata Hijab located in Paciran District, Lamongan Regency. The main problem faced by the partner is the suboptimal management of digital marketing, particularly in content strategy planning, posting consistency, and the utilization of TikTok Shop features, resulting in marketing activities that have not yet provided maximum impact on improving marketing performance. The implementation method of this community service employed a mentoring and training model, which included stages of interviews, observation, and documentation throughout the mentoring process. The results indicate that the planned and sustainable implementation of digital marketing strategies through TikTok Shop is able to increase brand awareness, expand promotional reach, enhance customer interaction, and positively impact product sales. The effectiveness of the community service program is influenced by posting consistency, visual content quality, digital communication understanding, and the partner’s responsiveness to customers. This community service confirms that TikTok Shop digital marketing assistance is an effective strategy in supporting the improvement of marketing performance of UMKM Izzata Hijab in the digital era.